Pengaruh Model Problem Based Learning dengan Pendekatan Pembelajaran STEM Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Septi Ardianti; Tanti Jumaisyaroh Siregar; Ammamiarihta Ammamiarihta (Educational Journal, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model with a STEM approach on students' mathematical problem-solving abilities in SPLDV material. This study used a quasi-experimental approach with a non-equivalent control group design. The subjects were eighth-grade students at MTs Swasta Lab IKIP Al-Wasliyah Medan, divided into two classes: an experimental class and a control class, each consisting of 26 students. The experimental class was taught using the PBL model with a STEM approach, while the control class used a conventional learning model. The instrument used was a mathematical problem-solving ability test. The results showed that the average posttest score for the experimental class was 73.08, while the control class was 59.62. The results of the Independent Sample t-Test show that the value of ????ℎ???????????????????? = 3.341 is greater than ???????????????????????? = 2.009 with a significance value of 0.002 < 0.05, so that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a significant influence of the application of the Problem Based Learning model with the STEM approach on students' mathematical problem-solving abilities.